Analysis and design of information system for the management of the “Domingo Savio” hotel. Strategic plan for the implementation of the guests management system - Vera Silva, Ricardo (2021)
Fil: Vera Silva, Ricardo. Universidad Católica "Nuestra Señora de la Asunción". Facultad de Ciencias Económicas; Paraguay.